Apolipoprotein C1 -317H1/H2 and the rs4420638 genetic variations and risk of gestational diabetes mellitus in Chinese women: a case-control study - Ma, Wandi; Guan, Linbo; Liu, Xinghui; Wu, Yujie; Zhu, Zhengting; Guo, Yuwen; Fan, Ping; Bai, Huai (Frontiers in Endocrinology, 2025)
BackgroundDyslipidemia and oxidative stress are key components in the pathophysiology of gestational diabetes mellitus (GDM), yet the contribution of genetic factors to these metabolic disturbances remains unclear. This study aimed to investigate the relationship between two lipid-related genetic polymorphisms, apolipoprotein C1 (apoC1) gene -317H1/H2 (rs1568822) and rs4420638, with GDM risk and lipid profiles and oxidative stress markers in Chinese populations.MethodsThe apoC1 -317H1/H2 and rs4420638 polymorphisms were genotyped in 734 GDM patients and 1,102 control subjects. Genetic association with GDM risk and related traits were also analyzed,ResultsThe distribution of genotype and allele in both polymorphisms were similar between the two groups. However, the combined H1H1/AG+GG genotype was significantly more frequent in women with GDM than in the control group. GDM patients who carried H1H1/AG+GG genotype were 1.97-fold increased risk to develop GDM (95% CI: 1.140-3.414, P = 0.015). H2 allele correlated with decreased levels of low-density lipoprotein cholesterol (LDL-C), apoB and lower atherogenic index (AI) in both groups, in addition to the GDM group also with lower total cholesterol (TC), whereas the G allele of rs4420638 correlated with increased triglyceride and decreased apoA1 levels.ConclusionApoC1 gene polymorphisms associate with GDM risk and affect the lipid profile. The combined H1H1/AG+GG genotype of the apoC1 gene polymorphisms appears to augment the propensity to develop GDM, while the rs4420638 polymorphism links to adverse lipid components in the patients. Further genetic studies to add information beyond the traditional risk factors in GDM and to identify risk genotypes will help in early prediction and identification of at-risk patients.